Application of the IML Resistograph to the infield assessment of basic density in plantation eucalypts. Issue 3 (3rd July 2018) - Downes, G. M.; Lausberg, M.; Potts, B. M.; Pilbeam, D. L.; Bird, M.; Bradshaw, B.
ABSTRACT: Average bark-to-bark resistance of the IML Resistograph PD400 (hereafter referred to as 'Resi') was found to provide strong linear correlations with the basic density of 12-mm-diameter increment cores taken from standing plantation eucalypt trees. Relationships between Resi values and approximately 2 000 cores (predominantly Eucalyptus globulus but some E. nitens ) were examined across seven studies (representing samples from nine distinct sites) in Tasmania, Victoria and Western Australia. Custom-written software was developed to process the Resi traces to automatically perform a linear baseline correction of the trace, and extract: over-bark and under-bark diameter bark thickness average resistance of the bark-to-bark (under-bark) trace average resistance of the outer 50 mm on the entry and exit side of the traces. Baseline correction was needed to counter the variable effects among trees of needle drag across the diameter, largely a function of tree diameter and wood density. Individual traces were collected in less than 20 s tree −1 . The sampling conditions of 150 cm min −1 speed of forward movement (feed speed) and 3 500 revolutions per minute (rpm) were identified as optimal for the plantation eucalypts studied. The relationship between different feed speeds and rpm were linear and coefficients determined to allow average Resi resistance to be converted to a common set of sampling conditions. A simple linear regression was identified in each study to define a slope and intercept to convert the Resi values to basic density and determine the variance between them. Resi traces from different studies were not always collected using the same instrument and this is believed to explain most of the between-study variance in slope and intercept. Trace processing software was built into a web-based package that is available to make trace processing easy, with defined variables downloadable for use in routine plantation assessment. Users can change the default slope and intercept values to suit their individual instruments or species as required. Further work is required to fully define the effects of instrument, site and species on these relationships. The IML Resistograph PD400 was found to be an accurate and quick (40–70 trees hour −1 person −1 ) infield tool for estimating diameter and wood density in standing trees. When combined with automated, web-based processing software the methodology is among the lowest cost options conceivable for wood density assessment of plantation eucalypts.